A case report of Rosai Dorfman disease - Waghray, Jyotika; Waghray, Pradyut (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Rosai-Dorfman’s disease also known as sinus histiocytosis with massive lymphadenopathy (SHML) is characterized by distorted lymph node architecture with marked dilation of lymphatic sinuses occupied by numerous lymphocytes, as well as histiocytes with vesicular nucleus and abundant clear cytoplasm with phagocytized lymphocytes or plasma cells, also known as ‘emperipolesis’. This disease of unknown etiology progresses with a benign prognosis strictly and only when an early diagnosis and treatment is made. A late diagnosis and a generalized lymph node involvement contribute to a poor prognosis. We reported a case of a 29-year-old Indian female with a 4-month history of painful unilateral cervical mass and low-grade fever with the final diagnosis of Rosai-Dorfman disease. The final diagnosis was made by fine needle aspiration (FNA) biopsy of the cervical lymph node. In conclusion, FNA biopsy can be enough to make the diagnosis in most cases due to the distinct cytological features of SHML, thereby avoiding more invasive approaches that potentially are unnecessary.